The Potential Leaves of Porang (Amorphophallus muerelli blume) as Antioxidant and Antibacterial Escherichia coli and Salmonella typhi - Susani Erikania; Vivi Rosalina (Jurnal Biologi Tropis, 2022)
Porang are known as plants that have high economic value. This plant was produced tubers which are widely used by industry as paper adhesives, cotton fabric paint, wool and the flour can be used as a substitute for agar. The Increased of this plant cultivation produced leaves which were not utilized. This study sought to determine whether porang leaves could be used as an antioxidant and antibacterial against Salmonella thypii and Escherichia coli.  Porang leaves extract was determine as antioxidant used DPPH method with quercetin as a standard and extract concentrations of 100 ppm, 200 ppm, 300 ppm, 400 ppm, 500 ppm. Antibacterial test using disc diffusion method with positive control of ciprofloxacin 5 μg/disk, negative control of DMSO 10% and extract concentration of 10%, 20%, 40%, 80% and 100%. The results of this study indicate that porang leaves have potential as antioxidants and antibacterials. Porang leaves extract had the greatest antibacterial activity against Salmonella thypii at concentration of 100% with inhibition zone of 11.10 mm in the strong category. While the Escherichia coli bacteria at concentration of 100% was 8.10 mm in the medium category. Porang leaf extract has weak antioxidant activity with an IC50 value of 466.07 ppm compared to the standard quercetin IC50 value of 11.23 ppm with a very good category.